KONSTRUKSI TEOLOGI HINDU DALAM UPAYA MENGHILANGKAN BUDAYA MENGEMIS PADA MASYARAKAT MUNTI GUNUNG KECAMATAN KUBU KABUPATEN KARANGASEM - I Wayan Sunampan Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This research departs from the cultural phenomenon of begging in the Munti Gunung community which has been going on for a long time, and has even become a label that has been passed down from generation to generation. Various kinds of efforts have been made by the government to overcome this problem, but it has not had the maximum impact, even this culture of begging still exists. Departing from this problem, the authors try to conduct a study to look critically at the culture of begging from society with sociological and theological approaches, so that they can see the culture of begging as a whole. As for the results of the data analysis obtained, namely the culture of begging is inseparable from the socio-graphic conditions of the Munti Gunung community which can be said to be arid and located in the interior and hills, this is a factor that causes the community to experience difficulties in processing nature to fulfill economic aspects. This culture of begging also creates a contradiction between religious and social issues. On the religious aspect, the culture of begging is the impact of a curse from the goddess Danu from past events. Then from the social aspect, begging is a social problem that disturbs the image of the Balinese people. In overcoming the culture of begging, people are starting to become aware of it by building a theological attitude, namely by various activities that build people's spirit and motivation to improve. This is of course also supported by various parties. The problems and efforts made certainly require a long process.